E-Learning Implementation Challenges and Impact on Education System of Pakistan - Asma, Shahzadi; Qazi Naeem, Alam (2021)
The proposed study discusses the various parameters of the interest of the student towards e-learning by analyzing the primary data of the students' feedback from a questionnaire. It analyses the e-learning process among students who are using this tool in their school colleges. A stratified sampling method has been adopted for a sample size of 200 and the data has been collected from different grade students of the school, college, and universities of the Pakistan. Further, the study provides a detailed discussion of the challenges of adopting eLearning and its impact on the ordinary education system during a Corona Virus disease outbreak around the world and especially in Pakistan. It explains how the educational institution faces the challenges of immediate and unplanned switching from ordinary learning methods to e-learning approaches in this dire situation. This article will help educational professionals, students, and policymakers for new age education.